Modelling and Order of Acoustic Transfer Functions Due to Reflections from Augmented Objects. (21st December 2006) - Kuster Kuster, Martin Martin; de Vries de Vries, Diemer Diemer
Abstract : It is commonly accepted that the sound reflections from real physical objects are much more complicated than what usually is and can be modelled by room acoustics modelling software. The main reason for this limitation is the level of detail inherent in the physical object in terms of its geometrical and acoustic properties. In the present paper, the complexity of the sound reflections from a corridor wall is investigated by modelling the corresponding acoustic transfer functions at several receiver positions in front of the wall. The complexity for different wall configurations has been examined and the changes have been achieved by altering its acoustic image. The results show that for a homogenous flat wall, the complexity is significant and for a wall including various smaller objects, the complexity is highly dependent on the position of the receiver with respect to the objects.